202k views
5 votes
50 points urgent please put all the steps to finish

50 points urgent please put all the steps to finish-example-1
User Maro
by
5.7k points

2 Answers

3 votes
So for this you need to opinionated a variable from the equation. So I’ll do y. Sometimes both variables. But I hope this helps. This is how I do it but I do it different I wrote the x and y values in the upper left hand cornner
50 points urgent please put all the steps to finish-example-1
User Greg Lowe
by
4.9k points
2 votes

Answer: x=2

3x+2y=12 and y=2x-1 so you already know what y equals. Substitute y into the first problem.

Step-by-step explanation: 3x+2y=12 will turn into

3x + 2(2x-1) = 12 now multiply the 2 on the outside to the inside numbers

3x + 4x - 2 = 12 then combine the x's

7x - 2 = 12 after you are going to add 2 to both sides

+2 = +2 (the negative 2 and positive 2 cancel each other out)

7x = 14 then divide 7 to both sides which gets you 2

If you place 2 back into y=2x-1 you'll get y=2(2)-1 which is y=4-1 so y=3

so 3x+2y=12 will become 3(2) + 2(3) = 12

User Ozan Yurtsever
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.